Pedagoški vidiki poučevanja nejezikovnih predmetov v tujem jeziku - Brumen, Mihaela; Kolbl Ivanjšič, Polonca; Pšunder, Mateja (Revija za elementarno izobraževanje, 2015)
Pedagogical Aspects of Subject Teaching in a Foreign Language. Functional multilingualism, as a linguistic image of Europeans, dictates the knowledge and use of multiple languages among people. The modern dual-focused educational approach known as CLIL (Content and Language Integrated Learning), enables exactly this at different levels of education. This paper presents the academic/educational, emotional, cognitive and intercultural dimensions of subject teaching in a foreign language. The first part of the paper introduces some recent studies which confirm the effects of CLIL in conjunction with the above mentioned dimensions. The second part of the paper describes an example of subject teaching in a foreign language at one of the primary schools in Slovenia. On the basis of student-feedback, it describes an example of CLIL learning and teaching that we consider good practice.